2020
DOI: 10.1159/000506411
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Cellular Repressor of E1A-Stimulated Genes Protects against Renal Fibrosis in Dahl Salt-Sensitive Rats

Abstract: Background: Human cellular repressor of E1A-stimulated genes (CREG) is a secreted glycoprotein that attenuates angiotensin II-induced hypertension, alleviates myocardial fibrosis, and improves heart function. However, the role of CREG in high-salt (HS) diet-induced hypertensive nephropathy is unclear. Methods: To determine the effects and molecular mechanisms of CREG in HS diet-induced hypertensive nephropathy, we established a hypertensive nephropathy animal model in Dahl salt-sensitive (SS) rats fed a HS die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…On the basis of understanding the interaction network of "drug-target-disease, " the intervention and influence of drugs on the complex pathological network were observed through network analysis, and the interaction relationship between each node of the network was observed intuitively and clearly by using large-scale data integration, which provided a new platform for the mechanism target research of complex diseases (13,14). The results of network pharmacology research showed that the core targets of VK2 in the treatment of salt-sensitive hypertension included as ALB, REN, IL10, SERPINE1, SRC, EGFR, F2, MAPK8, ESR1, and PLG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of understanding the interaction network of "drug-target-disease, " the intervention and influence of drugs on the complex pathological network were observed through network analysis, and the interaction relationship between each node of the network was observed intuitively and clearly by using large-scale data integration, which provided a new platform for the mechanism target research of complex diseases (13,14). The results of network pharmacology research showed that the core targets of VK2 in the treatment of salt-sensitive hypertension included as ALB, REN, IL10, SERPINE1, SRC, EGFR, F2, MAPK8, ESR1, and PLG.…”
Section: Discussionmentioning
confidence: 99%
“…The network construction of VK2-targets-pathways-disease network was conducted using Cytoscape_v3.7.1. The detailed methods were described in previous reports (13,14).…”
Section: Network Construction Of Vitamin K 2 -Targets-pathways-diseasmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Liu et al [11] indicated that the upregulation of CREG reduced human umbilical vein endothelial cells apoptosis induced by high glucose and high palmitate. Besides, a recent study found that administration of recombinant CREG prevented renal cell apoptosis and protected renal tissue against kidney injury and brosis with a high-salt diet [12]. Most recently, accumulating evidence revealed a critical role of CREG in ischemia-reperfusion injury [13].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has identified that CREG overexpression suppresses pathological apoptosis in human vascular smooth muscle cells, which can be attributed to the activation of the vascular endothelial growth factor (VEGF)/PI3K/AKT signaling pathway (Wang et al, 2011). Similarly, recombinant CREG treatment inhibited apoptosis of the kidney cells, relieved renal fibrosis, and thereby improved renal function in high‐salt diet‐induced hypertensive nephropathy (Liu et al, 2020). The above background suggested CREG might play an essential role in neuronal apoptosis during neonatal HIE occurrence and development, which could possess the ability to contribute to neonatal HIE treatment.…”
Section: Introductionmentioning
confidence: 99%